BACK TO BASIC: THEORIES AND MODELS OF COMMUNICATION - Anna Lynn Abu Bakar; Wardatul Akmam Din; Romzi Ationg; Suyansah Swanto, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Communication plays a vital role in our everyday lives. Communication that is effective can aid in the resolution of numerous issues and problems. Therefore, effective communication skills are required. To be able to interact with others, it is necessary to develop communication skills and the ability to express one's thoughts and connect with others. This paper aims to look into communication theories and models in order to gain a deeper understanding of communication's origins. The purpose of this paper is to present the origins of communication and how this may influence students' willingness to communicate in the classroom, outside of the classroom, and on digital platforms.